Development of Integrated Citizens The Institution Community Based on The Principle of Protection Towards Social Reintegration - Zainab, Nina; Eleanora, Fransiska Novita (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2023)
An inmate is someone who is deemed guilty and must serve a sentence in prison based on a verdict or decision from a judge with permanent legal force (inkracht) based on evidence and evidence. Development for prisoners cannot be separated from their rights both inside and outside prison, with the aim of independence which is also in the nature of development as it is directed towards development with the mentality and character of being a complete human being, as well as pious, and also responsible for oneself. , also for families, and for society, and talents and skills can be developed so that they play an active and responsible role in society in the future when free, related to social reintegration. Protection, which is the principle in which inmates are treated in correctional institutions in order to ensure that society can be protected from the possibility of repeating criminal acts in the form of crimes or violations, also provides provisions for life for inmates so that they become useful citizens in society. The research method is normative juridical by referring to statutory regulations, as well as existing literature based on literature study. The result is that social reintegration can provide changes in the development of inmates so that their attitudes and behavior become better and they can have abilities in community life.